2017
DOI: 10.1038/s41598-017-10838-5
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase SIRT6 blocks myostatin expression and development of muscle atrophy

Abstract: Muscle wasting, also known as cachexia, is associated with many chronic diseases, which worsens prognosis of primary illness leading to enhanced mortality. Molecular basis of this metabolic syndrome is not yet completely understood. SIRT6 is a chromatin-bound member of the sirtuin family, implicated in regulating many cellular processes, ranging from metabolism, DNA repair to aging. SIRT6 knockout (SIRT6-KO) mice display loss of muscle, fat and bone density, typical characteristics of cachexia. Here we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 81 publications
(104 reference statements)
5
45
1
Order By: Relevance
“…Our data showed that Ex‐4 treatment activates both PKA and AKT signalling pathways and inhibits phosphorylated NF‐κB protein expression. Activated AKT signalling can directly suppress the phosphorylated protein level of NF‐κB in C2C12 myotubes, which may in turn reduce the binding of NF‐κB to promoter regions of MSTN . As expected, Ex‐4 treatment decreased MSTN protein expression and Ex‐9 or GLP‐1R knockdown inhibited this effect, suggesting that the GLP‐1R‐mediated signalling pathway might be involved in regulation of MSTN expression.…”
Section: Discussionsupporting
confidence: 64%
“…Our data showed that Ex‐4 treatment activates both PKA and AKT signalling pathways and inhibits phosphorylated NF‐κB protein expression. Activated AKT signalling can directly suppress the phosphorylated protein level of NF‐κB in C2C12 myotubes, which may in turn reduce the binding of NF‐κB to promoter regions of MSTN . As expected, Ex‐4 treatment decreased MSTN protein expression and Ex‐9 or GLP‐1R knockdown inhibited this effect, suggesting that the GLP‐1R‐mediated signalling pathway might be involved in regulation of MSTN expression.…”
Section: Discussionsupporting
confidence: 64%
“…The high‐fat diet significantly reversed these atrophy features (Figure and Figure ). It was reported recently that SIRT6 can block myostatin expression and the development of muscle atrophy (Samant et al, ). The high‐fat diet efficiently attenuated the overexpression of myostatin caused by the SIRT6 deficiency (Figure f).…”
Section: Resultsmentioning
confidence: 98%
“…SIRT6 deficiency in mice causes a severe metabolic disorder, which leads to multi‐organ atrophy, premature aging features, and death within 1 month. Recently, it was reported that SIRT6 can block myostatin expression and SIRT6 deficiency‐induced muscle atrophy (Samant et al, ). In our experiments, the high‐fat diet effectively reversed the SIRT6 KO‐induced shortening of the lifespan, multi‐organ atrophy, premature aging, and metabolic abnormalities both in male and female mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that the expression of SIRT6 may form the basis of a new therapeutic strategy to reduce muscle wasting in ageing‐associated diseases (Samant, Kanwal, Pillai, Bao, & Gupta, ). Furthermore, SIRT6 negatively regulates the expression of myostatin via the suppression of nuclear factor‐κB signalling (Samant et al., ). In particular, activation of exercise‐dependent SIRT1 in skeletal muscle provides protection against muscle weakening and atrophy induced by disuse and ageing‐related diseases (Canto et al., ; Lee & Goldberg, ).…”
Section: Discussionmentioning
confidence: 99%